Functional Status in Older Intensive Care Unit Survivors. (January 2020) - Tang, Hsin-Ju; Tang, Hsin-Yi (Jean); Chang, Chia-Ming; Su, Pei-Fang; Chen, Ching-Huey
Older ICU survivors are often challenged with clusters of geriatric syndromes and functional decline. The purpose of this study was (a) to assess patterns of geriatric syndromes and functional status from admission to 6 months post discharge and (b) to examine the predictors of longitudinal functional status. This is a prospective cohort study. Demographic information, clinical variables, geriatric syndromes, and functional status were collected longitudinally. A total of 192 medical ICU older adult survivors were included in the analysis. Factors associated with reductions in functional status over 6 months were (a) institutionalized prior to hospitalization, (b) pressure sore before admission, (c) existing delirium, (d) impaired mobility at baseline, (e) increased APACHE II score upon ICU admission, and (f) use of mechanical ventilation during the ICU stay. Importantly, overweight was the only factor that was associated with increased functional level over 6 months.